Răspuns :
√2 ( x+2√2) + √3 ( 1-x√2) = 1+2√3√2x+2*2+√3-x√6=1+2√3
√2x+4+√3-x√6=1+2√3
√2x-x√6=1+2√3-4-√3
x(√2-√6)=-3+√3
x= -3+√3/ √2-√6 !! Amplifici cu √2+√6
x=(√2+√6)(-3+√3) / (√2-√6)(√2+√6)
x=-3√2+√6-3√6+√18 / (√2)²- (√6)²
x= -3√2-2√6+3√2 / 2-6
x= -2√6 / -4 !! Minus impartit la minus = +
x=2√6/4 !! simplifici cu 2
x= √6/2
√2x+4+√3-x√6=1+2√3
√2x-x√6=1+2√3-4-√3
x(√2-√6)=-3+√3
x= -3+√3/ √2-√6 !! Amplifici cu √2+√6
x=(√2+√6)(-3+√3) / (√2-√6)(√2+√6)
x=-3√2+√6-3√6+√18 / (√2)²- (√6)²
x= -3√2-2√6+3√2 / 2-6
x= -2√6 / -4 !! Minus impartit la minus = +
x=2√6/4 !! simplifici cu 2
x= √6/2